2019
DOI: 10.3390/agronomy9040182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tillage Systems on Spatial Variation in Soil Chemical Properties and Winter Wheat (Triticum aestivum L.) Performance in Small Fields

Abstract: To investigate how tillage intensity modifies the small-scale spatial variability of soil and winter wheat parameters, field trials were conducted on small plots (12 m × 35 m) in three temperate environments in the Swiss midlands: Zollikofen in 1999 (loamy silt soil; Gleyic Cambisol) and Schafisheim in 1999 and in 2000 (sandy loam soil; Orthic Luvisol). Total soil nitrogen (Ntot), total carbon (Ctot) and pH were assessed after harvest. A regular nested grid pattern was applied with sampling intervals of 3 m an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…Opposite relationships were found in the deeper soil layer-15-30 cm. The distribution of nutrients in soil affects their uptake and plant chemical composition (Lüder et al 2019;Virk et al 2019). In the present study, under no-tillage conditions a higher seed protein content and a lower fat content were found compared to plough tillage, respectively by 0.5 and 0.4% (Tables 4 and 5).…”
Section: Yield and Protein And Fat Content In Soybean Seedssupporting
confidence: 51%
See 2 more Smart Citations
“…Opposite relationships were found in the deeper soil layer-15-30 cm. The distribution of nutrients in soil affects their uptake and plant chemical composition (Lüder et al 2019;Virk et al 2019). In the present study, under no-tillage conditions a higher seed protein content and a lower fat content were found compared to plough tillage, respectively by 0.5 and 0.4% (Tables 4 and 5).…”
Section: Yield and Protein And Fat Content In Soybean Seedssupporting
confidence: 51%
“…The results of other authors' research are not unequivocal. Lüder et al (2019) showed winter wheat grain to be less protein-rich under NT in comparison to CT, while according to Woźniak and Soroka (2014) triticale grain contained more protein under NT conditions than under CT. Gao et al (2009), however, obtained an increase in fat yield per hectare for non-tilled soybean.…”
Section: Yield and Protein And Fat Content In Soybean Seedsmentioning
confidence: 96%
See 1 more Smart Citation
“…Under the reduced tillage system and direct drilling, nutrients are unevenly distributed due to their greater accumulation in the top soil layer [5,7,17,55,[60][61][62]. Under such tillage conditions, the accumulation of crop residues in the surface soil layer promotes a higher concentration of P, K, and Mg, compared with conventional tillage [7,16,31,63].…”
Section: Discussionmentioning
confidence: 99%
“…In the fields of agricultural farms, it is rather impossible [73]. The variation in the physical, chemical, and/or biological properties of soil and the yield of crops is found not only in large-acreage fields, but also in small fields [74][75][76]. For that reason, each agrotechnical practice that decreases the variation in the conditions and plant production results at the scale of the field is desired.…”
Section: Discussionmentioning
confidence: 99%